PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK KANCING GEMERINCING UNTUK MENINGKATKANMOTIVASI BELAJAR SISWA PADA MATAPELAJARAN EKONOMI KELAS VIII DI MADRASAH TSANAWIYAH AL–MANAR PUJUD ROKAN HILIR - Asri '; Makhdalena '; Hendripides ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The background of the problems in this study is the lack of student motivation. This study aims to determine the application of cooperative learning techniques clatter of studs in improving students' motivation on the subjects of economy class VIII MTs Al-Manar Pujud Rokan HilirThis research is a classroom action research (PTK) is conducted in two cycles. Each cycle consists of two meetings. The subjects in this study the number of eighth grade students with 26 students. To be successful classroom action research. The researchers set the stage that action planning, action, observation and reflection. The instrument pengumupulan observation sheet data that teacher and student activity observation sheet motivation to learn. Based on the results, it can be concluded that the adoption of cooperative learning techniques clatter of studs can increase students' motivation on the subjects of economy based on indicators of student motivation. The average percentage of student motivation at the first meeting reached 55.77% with unfavorable category, and then increased in the second meeting of the first cycle with an average score of 67.31% with enough category. While on the second cycle, the students' motivation has increased to 74.36% with enough categories and the second meeting reached 83.33% in both categories.Key Words: The implementation of cooperative learning model clattering studs tecniques to improve students’ motivation.